PENERAPAN AKUNTANSI PENGAKUAN ASET TETAP PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN MINAHASA - Aring, Aprico; Tinangon, Jantje J.; Elim, Inggriani (Universitas Sam Ratulangi, 2020)
Assets can still be used for mutual interests between the government and the general public and can be directly felt for their usefulness. Recognition of fixed assets is regulated in Republic Indonesian Government Regulation No. 71 of 2010 concerning Public Accounting Standards Statement which includes the accrual basis as applicable SAP. This study aims to determine the extent on application of accounting for the recognition of fixed assets. The method of analysis used in this study is a descriptive method in which the purpose of each data collected is analyzed and drawn a conclusion and the type of research conducted is descriptive qualitative. The results of the study found that the process of recognizing fixed assets at the Minahasa District Financial and Asset Management Agency is in accordance with applicable regulations.